Polymeric Organo-Silane Coatings for Aluminum Alloy Corrosion Protection by Self-Assembled Metho - Yabin Wang; Yanni Li; Fang Wang (E-Journal of Chemistry)
The protective performances of coating formed by organo-silane with a linear alkyl chain for promoting aluminum alloy corrosion protection were evaluated by electrochemical techniques. The coatings were self-assembled in the hydrolyzed hydroalcoholic bath of n-octyltriethoxysilane (OS) and cured at hot air oven by different time. The coatings prepared by the less self-assembled number and shorter cured time, were always porous and scarcely protective. On the contrary, those built by the more self-assembled number and the longer cured time had higher coverage on aluminum surface and favorable corrosion resistant property. The best results were obtained when n-octyltri-ethoxysilane (OS) was hydrolyzed 25 h, self-assembling of OS was conducted for five times and the multi-layers were cured at 120 for 1∼2 hours. In this case, the thicker, high cross-linked and more scarcely defective layer was formed on aluminum alloy surface.